A switched capacitor amplifier-based readout IC for diode-based infrared sensor. (October 2019) - Li, Yao; Ye, Mao; Zheng, Xiaoxiao; Zhao, Gongyuan; Zhao, Yiqiang
Abstract: In this paper a switched capacitor amplifier-based readout integrated circuit for diode-based infrared sensor is presented. Compared with the conventional integrator-based amplifier, the proposed switched capacitor amplifier achieves the PVT-insensitivity voltage gain. The noise performance is carefully analyzed and optimized, and the simulated total input equivalent noise reaches 8.15 μV within 50 KHz bandwidth. To reduce the power consumption, the two level switch matrix and pulse powered column amplifier are proposed in the design. The methods of dummy metal line and current splitting DAC array are introduced to implement on-chip non-uniformity correction. The chip has been realized with a 0.35 μm 2-poly and 4-metal CMOS technology and occupies an area of 70 mm 2 consuming 185 mW from a 5 V power supply. The non-uniformity of output voltage is improved by 78.05% with the help of on-chip non-uniformity correction.